2014
DOI: 10.5901/mjss.2014.v5n20p497
|View full text |Cite
|
Sign up to set email alerts
|

The Entrepreneurial Orientation of Immigrant Entrepreneurs in South Africa

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Businesses that are entrepreneurially oriented are innovative, proactive and good in risk taking (Boso, Story and Cadogan 2013). Additionally, Fatoki and Oni (2014) measured the EO of immigrant entrepreneurs in South Africa using three elements namely innovativeness, risk taking and proactiveness. EO can also be measured using four attributes namely (1) risk taking, (2) autonomy, (3) innovativeness and (4) competitive aggressiveness (Lee and Lim 2009).…”
Section: Definition Of Entrepreneurial Orientationmentioning
confidence: 99%
“…Businesses that are entrepreneurially oriented are innovative, proactive and good in risk taking (Boso, Story and Cadogan 2013). Additionally, Fatoki and Oni (2014) measured the EO of immigrant entrepreneurs in South Africa using three elements namely innovativeness, risk taking and proactiveness. EO can also be measured using four attributes namely (1) risk taking, (2) autonomy, (3) innovativeness and (4) competitive aggressiveness (Lee and Lim 2009).…”
Section: Definition Of Entrepreneurial Orientationmentioning
confidence: 99%
“…Focusing on entrepreneurs' ties to their home country, studies have found that immigrant entrepreneurs' mobilize networks to access financial resources, social support, information, and capabilities to enhance their competitive advantage (Saxenian 2002;Landolt 2001;Fatoki and Oni 2014). Highlighting the nature and role of dual affiliations in immigrants' entrepreneurial processes, Chen and Tan (2009) examine the structure and impact of Bglocalized^networks, networks with local and global connections, in the transnational entrepreneurship process.…”
Section: Literature Reviewmentioning
confidence: 97%
“…On the other hand, according to Kabui &Maalu (2012) [5] , there is no significant difference in the perception of entrepreneurship between students who had prior exposure to business studies at school and those who had not studied the subject. Fatoki & Oni (2014) [2] remarked that in South Africa, the skills and the knowledge required to become an entrepreneur should be encouraged among young people through education. Tong et al (2011) [12] found that the need for achievement, family business background, and subjective standards all predicted entrepreneurial intention, with the exception of the desire for independence.…”
Section: Review Of Literaturementioning
confidence: 99%